Valery Bryusov's world-modeling universals: the apperceptional base as the tool of world-modeling - Shuiskaya Yu.V, Kruglova T.S., Larina N.A., Pinaev S.M., Troshkin Yu.V., (Opción, 2019)
The article is devoted to the analysis of world-modeling universals in the fantastic story "Night Journey" by Valery Bryusov through case study as one of the qualitative research methods. The study posed the issue of this work relationship with the novel "Fiery Angel" by the same author. Due to the laconic characterization of the space in which the narrator is located, the apperception base and the information in presupposition are of primary importance as a world-modeling instrument in this work